Landrace renaissance in the mountains: Experiences of the Beej Bachao Andolan in the Garhwal Himalayan region, India - Singh, Vir; Jardhari, Vijay (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
The development of on-farm conservation of agro biodiversity is of particular significance in inaccessible, fragile, and risk-ridden mountain areas, such as the Garhwali Himalayan Region in India. Having experienced the negative impact of conventional institution-led breeding programs (that negligee farmers And their knowledge systems), the farmers in the mountains of Garhwali launched the Beej Bachao Andolan- the Save Seed Movement. The main objectives of this movement are to save the seeds of the landraces the farmers have developed over several generations of selection and to strengthen and restore Sustainable organic systems of farming.